Online Volunteering, A Way to Reduce Health Inequalities: A Review Study - Hamed Seddighi; Ibrahim Salmani (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Volunteering is a way for community participation and involving local social capital. Volunteering has potential to enhance wellbeing and reducing health inequalities. The aim of this study is to evaluate the effects of online volunteering on people well-being and reducing inequalities. Methods: In this narrative review, using related keywords 326 studies found in the initial search in PubMed, Sage, Springer, Google Scholar, Elsevier, PsycINFO and finally 57 studies selected for review. Results: The study found that virtual volunteering in organizations is a combination of offline and online volunteering, and fewer volunteers are online volunteering. One of the main features of online volunteering is the maximum use of time, and reduces travel time; this type of volunteering can be done 24 hours a day and seven days a week. Online volunteering can involve all people, including young people, the elderly, people with disabilities and disadvantaged groups and minorities, and one of the main benefits of this type of volunteering is that many people who cannot attend the organization can participate this way, volunteer services will be provided, as well as racial and ethnic discrimination in this type of volunteering can be reduced. Conclusion: Although online volunteering is developing globally, volunteer-based organizations have not yet adopted their strategies, rules and procedures for new volunteers. It seems online volunteering will also enable different groups to participate in activities and promote the health of different groups.